Tripylina safricana sp. nov. of the family Trischistomatidae (Nematoda: Enoplida), isolated from Weeping wattle (Peltophorum africanum) in South Africa - Shokoohi, Ebrahim; Masoko, Peter; Jansen Van Rensburg, Candice (Zootaxa, 2025)
During a research study on free-living bacterivorous nematodes carried out in South Africa, a notable population of Tripylina was discovered near the trunk of a Weeping wattle (Peltophorum africanum) in Sovenga Hills, Limpopo Province. The newly identified species, T. safricana sp. nov., is characterized by moderately short body length (500–770 µm; a = 23.1–26.6, b = 5.0–6.4, c = 17.3–24.1; c’ = 1.8–2.1, V = 57–69), solid outer labial setae (6–13 µm), a moderate sized dorsal tooth, two posteriorly positioned subventral denticles, a not cuticularized vagina, and a ventrally bent tail (25–44 µm) with a spinneret. Drawings, LM, and SEM photographs of the new species are provided.